AN ONTOLOGICAL APPROACH TO THE STORY OF BOĞAÇ HAN - Servet ŞENGÜL (Fırat University, 2019)
Beings brought the problems with themselves from the moment of their existence. The existence areas that also they are included in, will be the solution point of the problems. Hartmann's ontological areas, express the beings’ and the layers that their problems take part in. A problem belonging to the objective layer is perceived as belonging to personal layer in Boğaç Han story. Social judgements take over on the basis of a perception like this. The events which in Boğac Han story will be studied in terms of ontological layers.